Violence against women: Public health or law enforcement problem or both? - Williams, Emma (International journal of police science & management, 2018)
Despite ongoing research spanning many years, the police investigation of different forms of violence against women remains problematic. The most recent reviews exploring sexual and domestic violence suggest that vulnerable victims are not identified effectively and that this subsequently impacts on the investigation, level of attrition and provision of correct support for victims. The authors suggest that some of the current methods, aimed at improving these issues, can further compound problems within a police culture that often remains focused on narrow quantifiable performance targets. Violence against women involves a range of very complex issues and for most victims there are a number of vulnerabilities involved. Considering these factors are often related to public health concerns, the authors argue for a more consistent and joined-up approach to supporting victims through the criminal justice system. In the short term, this is necessary for keeping victims on board with the process and in the longer term, it is essential when dealing effectively with the broader issues impacting on their victimization. It is crucial given the current fiscal climate that these issues are dealt with universally, with a focus on sustainable outcomes. It is argued that integrating criminal justice and public health strategies will provide for more embedded and effective outcomes for victims.